1988
DOI: 10.1056/nejm198811103191902
|View full text |Cite
|
Sign up to set email alerts
|

Neu-Protein Overexpression in Breast Cancer

Abstract: Amplification of the neu proto-oncogene in breast cancer has been reported to correlate with the presence of lymph-node metastases and with a poor prognosis. We describe a method for the immunohistochemical detection of overexpression of neu protein on formalin-fixed paraffin-embedded tissue, with the use of two different monoclonal antibodies. In a group of tumors with a known neu-gene copy number, intense membrane staining of tumor cells was present in all tumors with neu-gene amplification. Of 189 tumors fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
90
2

Year Published

1989
1989
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 732 publications
(97 citation statements)
references
References 18 publications
5
90
2
Order By: Relevance
“…The percentage of tumours expressing the oncogene was consistently in the upper teens or low twenties which is entirely consistent with the results of other published studies using monoclonal or polyclonal antibodies on formalin fixed paraffin embedded sections (Thor et al, 1989;Paik et al, 1990;Walker et al, 1989; Van de Vivjer et al, 1988;Richner et al, 1990).…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The percentage of tumours expressing the oncogene was consistently in the upper teens or low twenties which is entirely consistent with the results of other published studies using monoclonal or polyclonal antibodies on formalin fixed paraffin embedded sections (Thor et al, 1989;Paik et al, 1990;Walker et al, 1989; Van de Vivjer et al, 1988;Richner et al, 1990).…”
supporting
confidence: 90%
“…Other studies have shown a significant effect of c-erbB-2 expression in the overall survival analysis but not in the recurrence free analysis (Paik et al, 1990;Parkes et al, 1990; Van de Vivjer et al, 1988), but only that by Paik shows c-erbB-2 expression to be independent prognostic significance on multivariate analysis.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…Correlations were found between membrane staining tumours and patho-histological findings such as tumour size (van de Vijver et al, 1988), negative ER-content (De Potter et al, 1989a;Thor et al, 1989;Wright et al, 1989a;Kommoss et al, 1990;De Potter et al, 1990), lymph node involvement (Berger et al, 1988;Thor et al, 1989), histological grade (berger et al, 1988;Barnes et al, 1988;Wright et al, 1989a) and survival time (Thor et al, 1989;Wright et al, 1989a).…”
mentioning
confidence: 89%
“…In addition, small cell and large cell variants may be distinguished, the latter usually being components of comedo carcinomas, which are most likely to over-express the protooncogene C-erbB-2 (van de Vijver et al, 1988). This introduces heterogeneity into the classification of DCIS and emphasises the need for large studies in order that sub-group analysis may be undertaken, so that invasive diathesis may be quantified.…”
mentioning
confidence: 99%